Análise integrada entre dados de expressão global de transcritos codificadores e de miRNAs em carcinomas de células escamosas de laringe - Lapa, Rainer Marco Lopez [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Laryngeal squamous cell carcinoma (LSCC) is one of the most common head and neck malignancies representing approximately 25% of the tumors located in this region. Risk factors associated to development of LSCCs include alcohol and tobacco consumption, family history of cancer and human papilloma virus (HPV) infection. Second primary tumors and metastasis are frequently observed in patients with LSCC. To date, no useful molecular markers have been described that can successfully predict disease progression and clinical outcome. In this context, large scale molecular studies enable a global analysis of tumor molecular alterations aiming to reveal biomarkers for early diagnosis, prognosis and response to therapy. LSCC samples were obtained from 88 untreated patients. Global gene (Array plataform 8x60K, Agilent Technologies) and miRNA expression (Array platform 8x60K, Agilent Technologies) profiles were evaluated in 35 and 33 samples, respectively (Test group, N=36). An independent group of samples (N=33, validation group) was included, being 33 formalin fixed and paraffin embedded tissue samples and 19 fresh frozen tissues. HPV genotyping using LINEAR ARRAY HPV Genotyping Test (Roche) was performed in tumor samples from test group. Only two cases were HPV16-positive. The expression analysis revealed 1,680 differentially expressed genes in tumors compared to normal tissue (pool of normal laryngeal samples from necropsies). The miRNA analysis revealed 89 miRNAs differentially expressed. Integrative transcriptome and miRNAs analysis data (negative correlation r<0) revealed a subset of altered genes associated with the degradation of extracellular matrix components (MMP3, MMP9, MMP10, MMP13, COL10A1 and COL3A1) and neoplastic processes (CAV1, ERBB4, HLF,HMGA2, HOXB6, KLF2, PDCD4, PPP1R3 and TOP2), as well as their putative miRNA regulators (hsa-miR-199b-5p, hsa-miR-218-5p, hsa-miR-29c-3p, hsa-miR-21-5p, hsa-miR-204-5p, hsa-miR-125b-5p, hsa-miR- ...

O carcinoma de células escamosas de laringe (CCEL) é um dos mais comuns que acometem a região da cabeça e pescoço, representando aproximadamente 25% dos tumores malignos desta localização anatômica. Os fatores de risco associados ao desenvolvimento deste tumor são o consumo de tabaco e álcool, história familiar e a infecção pelo vírus do papiloma humano (HPV) em uma parcela dos casos. A ocorrência de segundos tumores primários e metástases é frequentemente relatada nos CCEL. Entretanto, até o momento, não há marcadores moleculares úteis na prática clínica que sejam capazes de predizer a progressão e a evolução clínica da doença. Neste contexto, as plataformas de microarranjos de oligonucleotídeos (microarrays), têm possibilitado uma análise mais ampla na busca por marcadores de detecção precoce, progressão, resposta e risco de recorrência e metástase. Foram incluídos neste estudo 88amostras de CCEL de pacientes não tratados. O grupo teste foi composto por 35 CCEL avaliados previamente para expressão gênica global (8x60K, Agilent Technologies) e 33 para a expressão de miRNAs (plataforma Array 8x60K, Agilent Technologies). O grupo de validação foi formado por 33amostras fixadas em formalina e em blocos de parafina (FFPE) e 19 amostras de tumor a fresco. O grupo teste foi avaliado para genotipagem para o HPV (LINEAR ARRAY HPV Genotyping Test, Roche), resultando em dois casos positivos para HPV16. A análise de expressão de transcritos revelou 1.680 genes diferencialmente expressos comparados aos tecidos normais de laringe (necrópsias). A análise de expressão global de miRNAs revelou 89 miRNAs diferencialmente expressos na comparação entre tecido normal e tumoral. A integração entre os dados de transcritos codificadores e de miRNAs (correlação negativa r<0) revelou alterações recorrentes em um subgrupo de genes associados com a degradação de componentes da matriz extracelular...
Keywords: Carcinoma de células escamosas; Expressão gênica; Microarranjos de DNA; Virus do papiloma; Laringe - Câncer; DNA microarrays; Carcinoma, Squamous Cell